Serotonin Coordinates Responses to Social Stress—What We Can Learn from Fish - Backström, Tobias; Winberg, Svante (Frontiers in Neuroscience, 2017)
Social interaction is stressful and subordinate individuals are often subjected to chronic stress, which greatly affects both their behavior and physiology. In teleost fish the social position of an individual may have long-term effects, such as effects on migration, age of sexual maturation or even sex. The brain serotonergic system plays a key role in coordinating autonomic, behavioral and neuroendocrine stress responses. Social subordination results in a chronic activation of the brain serotonergic system an effect, which seems to be central in the subordinate phenotype. However, behavioral effects of short-term acute activation of the serotonergic system are less obvious. As in other vertebrates, divergent stress coping styles, often referred to as proactive and reactive, has been described in teleosts. As demonstrated by selective breeding, stress coping styles appear to be partly heritable. However, teleost fish are characterized by plasticity, stress coping style being affected by social experience. Again, the brain serotonergic system appears to play an important role. Studies comparing brain gene expression of fish of different social rank and/or displaying divergent stress coping styles have identified several novel factors that seem important for controlling aggressive behavior and stress coping, e.g. histamine and hypocretin/orexin. These may also interact with brain monoaminergic systems, including serotonin.